National qualifications framework: a qualitative approach towards the determination of the critical success factors. (2016) - Ramdass, Ramesh; Rahman, Abdul; Nellikunnel, Syriac
This study aims at identifying the Critical Success Factors (CSFs) of a National Qualifications Framework (NQF) and to subsequently develop a conceptual framework that could be used by policy-makers, as a tool to evaluate NQFs. The study was conducted in Mauritius and it comprised a content analysis followed by focus group in-depth interviews with a view to collect qualitative data. The exercise culminated in the identifications of CSFs and a conceptual framework for evaluating an NQF. The limitations of the study are its exclusive application in the Mauritian context. It remains tentative since it rests on narrow empirical evidence. The tool has to be tested with other NQFs so as to establish its suitability which leaves room for further research.